Challenges & Opportunities on Catalytic Conversion of Glycerol to Value Added Chemicals - Zaki Yamani Zakaria; Mazura Jusoh; Shams Shazid Kader; Siti Shawalliah Idris (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
With the rapid expansion of biodiesel industry, its main by-product, crude glycerol, is anticipated to reach a global production of 6 million tons in 2025. It is actually a worrying phenomenon as glycerol could potentially emerge as an excessive product with little value. Glycerol, an alcohol and oxygenated chemical from biodiesel production, has essentially enormous potential to be converted into higher value-added chemicals. Using glycerol as a starting material for value-added chemical production will create a new demand on the glycerol market such as lactic acid, propylene glycol, alkyl lactatehydrogen, olefins and others. This paper briefly reviews the recent development on value-added chemicals derived from glycerol through catalytic conversion of refined and crude glycerol that have been proven to be promising in research stage with commercialization potential, or have been put in a corporate marketable production. Despite of the huge potential of products that can be transformed from glycerol, there are still numerous challenges to be addressed and discussed that include catalyst design and robustness; focus on crude or refined glycerol; reactor technology, reaction mechanism and thermodynamic analysis; and overall process commercial viability. The discussion will hopefully provide new insights on justified direction to focus on for glycerol transformation technology. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).